Brazil’s social movement, women and forests: A case study from the National Council of Rubber Tappers - Shanley, P.; Silva, F.C. da; MacDonald, T. (2011)
This paper discusses the evolution of the roles of Brazilian women within one of the most prominent organizations of the Amazonian social movement, the National Council of Extractivist Populations (CNS). Between 1990 and 2009, Brazil’s Federal government created 89 extractive and sustainable development reserves in Amazonia, encompassing 24 million hectares. The conceptual underpinning of these reserves – sustainable and multiple-use forest management – are daily put into practice by thousands of rural Amazonian women. However, rural women’s relative role in forest policy is currently marginal. The Secretariat of Women Extractivists of CNS helped to transform women’s roles within CNS and the political hierarchy of extractive reserves from largely invisible to one of significance. Their work across sectors, cultivation of ties with the State, capacity building and acknowledgement of women’s cultural connections to forests, provide a strong foundation for an increasing role of Amazonian women to promote sustainable forest management and conservation.